2015
DOI: 10.1007/s10734-015-9946-y
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of self-efficacy to the relationship between personality traits and entrepreneurial intention

Abstract: Promoting farming work is crucial for sustainable economic development in Asian-Pacific rural areas. How to promote rural entrepreneurship has recently become a critical issue in agricultural education. This article reports the results of two subsequent studies. The first study confirmed the factor structures of the five-factor model of personality, the general self-efficacy scale, and the entrepreneurial intention scale. The second study tested the mediating effect of self-efficacy on the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 50 publications
11
146
1
13
Order By: Relevance
“…It is consistent with previous studies that reported that Emotional Stability [23], Conscientiousness [11,24], and Extraversion [23,24,65] were positively associated with entrepreneurial intention. Individuals who score high on Emotional Stability are usually defined as calm, cool, optimistic, and less emotional.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is consistent with previous studies that reported that Emotional Stability [23], Conscientiousness [11,24], and Extraversion [23,24,65] were positively associated with entrepreneurial intention. Individuals who score high on Emotional Stability are usually defined as calm, cool, optimistic, and less emotional.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding entrepreneurial implementation intention, Emotional Stability, Conscientiousness and Extraversion were positively related to it, while Agreeableness was negatively related to it. In addition, Wang et al [11] has indicated that dimensions of Big Five personality except for Emotional Stability played a considerable impact on the conviction aspect of entrepreneurial intention. Interpersonal Relationship, the one dimension of Big Six personality, was proposed based on the Chinese context [27].…”
Section: Big Six Personality Related To Entrepreneurial Intentionmentioning
confidence: 99%
See 3 more Smart Citations